If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 3x = 19 + x Solving 8 + 3x = 19 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 8 + 3x + -1x = 19 + x + -1x Combine like terms: 3x + -1x = 2x 8 + 2x = 19 + x + -1x Combine like terms: x + -1x = 0 8 + 2x = 19 + 0 8 + 2x = 19 Add '-8' to each side of the equation. 8 + -8 + 2x = 19 + -8 Combine like terms: 8 + -8 = 0 0 + 2x = 19 + -8 2x = 19 + -8 Combine like terms: 19 + -8 = 11 2x = 11 Divide each side by '2'. x = 5.5 Simplifying x = 5.5
| U-184=39 | | D/-2=36 | | 10(x-2)+8=12 | | 2x+2(x-5)=38 | | 4(x-8)-6x=-12 | | z^7+5z^6=0 | | 5m+m=12 | | 7/x=2-3/x | | 1078/14 | | 3r^2=2+7r | | 22=d-2 | | 4y+8=4 | | -4(5n+4)=-16-n | | -9w-4=14 | | x^2+3x-1=7x+22 | | -3(2p+4)=-15-5p | | (8x^-3y^3z^6)^1/3 | | 2=(v-7)(v-1) | | 8x-(3x-10)=30 | | 3*-4+6-2x=-2 | | (1+w)(4w+2)=0 | | k-5/7=2 | | 14(3/7x) | | 4n+2(10-n)=3 | | -21+(-56)= | | 5x+2(x+4)=-6 | | -6(6x+7)=-150 | | -21+56= | | 5x+4-7x=5+x-23 | | 5v=v+36 | | 0.05+0.35= | | -2-b=8 |